1999
DOI: 10.1063/1.479779
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a polymer surmounting a potential barrier: The Kramers problem for polymers

Abstract: We study the dynamics of a flexible polymer under a Kramers potential using the multidimensional barrier crossing theory. The activation free energy of the polymer evaluated by a lattice statistics yields the crossing rate as a function of chain length, temperature, and potential parameters. It is found that a long chain has an enhanced crossing rate due to the extended conformation of low free energy it has at the barrier, while a short chain has the crossing dynamics of a Brownian particle. A chain of interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…[51] and reference therein). Important results have been derived also for polymeric chains [35,36,42]. We want to stress that our aim here is not to improve such results: we are interested in analyzing the ability of a data-driven approach to reconstruct an activated dynamics.…”
Section: Polymer In a Double Wellmentioning
confidence: 99%
See 1 more Smart Citation
“…[51] and reference therein). Important results have been derived also for polymeric chains [35,36,42]. We want to stress that our aim here is not to improve such results: we are interested in analyzing the ability of a data-driven approach to reconstruct an activated dynamics.…”
Section: Polymer In a Double Wellmentioning
confidence: 99%
“…In this work, we revisit the Kramers' problem for a polymer in a double well [35,36] by using the evolution equations of proper RCs characterizing the slow dynamics of the chain. We model the polymer as a one-dimensional harmonic chain (the so-called Rouse chain).…”
Section: Introductionmentioning
confidence: 99%
“…In the last few decades considerable attention has been given to understand the thermally activated escape rate of polymers trapped in a potential well. [7][8][9][10][11][12] In particular Sebastian et al 2 and Sung et al 3,4 computed the crossing rate of a polymer as a function of the number of monomers, and the strength of interaction between individual monomers. They found that indeed the escape rate was a nontrivial function of these parameters.…”
Section: Introductionmentioning
confidence: 99%
“…1,[3][4][5][6] However, their transport and response properties are difficult to understand since they are multicomponent systems with features that depend on their size, flexibility, and shape. In the last few decades considerable attention has been given to understand the thermally activated escape rate of polymers trapped in a potential well.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27] Experimental examples of systems of this sort include polymer translocation, 28,29 where a polymer is crossing a membrane through a pore 30 or narrow µm-scale channels with traps. 31 Recent experiments by Liu et al involve the escape of a DNA molecule from an entropic cage.…”
Section: Introductionmentioning
confidence: 99%